Simultaneous determination of multiple components in rat plasma by UPLC-MS/MS for pharmacokinetic studies after oral administration of Pogostemon cablin extract - Zhu, Yameng; Ouyang, Huizi; Lv, Zhenguo; Yao, Guangzhe; Ge, Minglei; Cao, Xiunan; Chang, Yanxu; He, Jun (Frontiers in Pharmacology, 2024)
Pogostemon cablin (PC) is used in traditional Chinese medicine and food, as it exerts pharmacological effects, such as immune-modulatory, antibacterial, antioxidant, antitumor, and antiviral. In the present study, a reliable and sensitive ultra-high performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) method was developed and validated for the simultaneous determination of 15 prototype components (vanillic acid, vitexin, verbascoside, isoacteoside, hyperoside, cosmosiin, apigenin, β-rhamnocitrin, acacetin, ombuin, pogostone, pachypodol, vicenin-2, retusin, and diosmetin-7-O-β-D-glucopyranoside) in rat plasma after oral administration of the PC extract. Plasma samples were prepared via protein precipitation using acetonitrile, and icariin was used as the internal standard (IS). The intra-day and inter-day accuracies ranged from -12.0 to 14.3%, and the precision of the analytes was less than 11.3%. The extraction recovery rate of the analytes ranged from 70.6-104.5%, and the matrix effects ranged from 67.4-104.8%. Stability studies proved that the analytes were stable under the tested conditions, with a relative standard deviation lower than 14.1%. Therefore, the developed method can be applied to evaluate the pharmacokinetics (PK) of 15 prototype components in PC extracts of rats after oral administration using UPLC-MS/MS, providing reference value for the clinical application of PC.